Reviewing the past to stigmatize an uncomfortable present: Montano and other "heresiarchs" of the 2nd century from the Euclides da Cunha’s perspective About Antonio Conselheiro - Vasconcellos, Pedro Lima (Revista Crítica Histórica, 2022)
This article addresses how Euclides da Cunha, in Os sertões, approaches Christian leaders of the 2nd century, viewed as heretics, in order to stigmatize the figure of Antonio Conselheiro. Particularly, the millenarian tenor of Montano’s announcement, applied without further ado as an interpretative key to the Conselheiro’s preaching, serves to affirm the historical infeasibility of what Belo Monte (better known as Canudos) represented for the backlands’ men and women who bet their lives on it. It is highlighted how the author’s mistake is also due to prejudice with religion and with the central place it occupied in the Conselheiro’s project.